Ne pas aimer écrire (mais n’en penser pas moins) - Audrey Villiard (Communication)
I do not like writing, least of all when I have to follow the semantic, stylistic, and institutional codes of a research-creation PhD in communications. I do not like writing, and that applies equally to this article. All the codes that govern the process of writing a scientific article repulse me. The difference here is that rather than bypassing these constraints, I have decided to make understanding why I do not like writing the topic of the writing itself. While the goal of the exercise is to better understand myself, obviously I also want to be understood by others. I do not like writing because writing means using words to communicate. And for me, understanding the codes to communicate properly takes too much effort and energy. Why? Because I am autistic.